Молодежь в условиях общества риска - Закаблук, М. В. (ХНУРЕ, 2019)
The object of consideration in this article is the young generation in the high-risk society, and the associated social status of uncertainty. Theoretical approaches to understanding risk and prerequisites of their formation. Explain the concept of uncertainty from the point of view of modem sociological approach and considers the impact of risk on social interaction of young people in society.